2020
DOI: 10.3390/foods9010043
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid and Cholesterol Oxidative Products Generated in Hot Boned Beef Semimembranosus Muscle as Affected by Rigor Temperature, Ageing and Display Time

Abstract: The present study investigated the effect of processing parameters comprising rigor temperature, ageing and display time on conjugated linoleic acid (CLA) concentrations, stability and the development of cholesterol oxidation products in hot boned beef semimembranosus muscles. Meat samples, having attained rigor mortis at 5 °C and 25 °C, were vacuum packed and aged for 7 and 14 days and then displayed under aerobic conditions for 7 days at 4 °C. Lipid was extracted at each time interval then 1H NMR and GC-FID … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In the studies of other scientists, the dry matter content of M. longissimus muscle ranged from 20.52 to 26.84%, total fat content from 1.10 to 4.42%, protein content from 21.47 to 22.45, ash content from 1.00 to 1.11%, iron content from 14.2 -1 to 22.03 mg kg and cholesterol content from 50.86 to 88.00 -1 mg per 100 g (Brugiapaglia, Lussiana, & Destefanis, 2014;De Marchi et al, 2007;Jemeljanovs et al, 2006;Mateescu et al, 2013;Mungure et al, 2020;Nogalski et al, 2018;Somogyi et al, 2015;Wheeler et al, 1987). In our study, a higher dry matter and total fat content was obtained, but an iron content was lower.…”
Section: Slaughter Results By Bull Breedsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies of other scientists, the dry matter content of M. longissimus muscle ranged from 20.52 to 26.84%, total fat content from 1.10 to 4.42%, protein content from 21.47 to 22.45, ash content from 1.00 to 1.11%, iron content from 14.2 -1 to 22.03 mg kg and cholesterol content from 50.86 to 88.00 -1 mg per 100 g (Brugiapaglia, Lussiana, & Destefanis, 2014;De Marchi et al, 2007;Jemeljanovs et al, 2006;Mateescu et al, 2013;Mungure et al, 2020;Nogalski et al, 2018;Somogyi et al, 2015;Wheeler et al, 1987). In our study, a higher dry matter and total fat content was obtained, but an iron content was lower.…”
Section: Slaughter Results By Bull Breedsmentioning
confidence: 99%
“…Cholesterol is considered a risk factor for cardiovascular disease and promotes atherosclerotic changes in the body. Studies performed so far have shown that the cholesterol content of meat is mainly influenced by the feeding stuffs used in cattle fattening and that the breed has no significant effect on its changes (Brugiapaglia, Lussiana, & Destefanis, 2014;Mungure et al, 2020;Wheeler et al, 1987).…”
Section: Introductionmentioning
confidence: 99%